Bioactive MOFs Based Theranostic Agent for Highly Effective Combination of Multimodal Imaging and Chemo‐Phototherapy. Issue 14 (16th June 2020) - Zhu, Yuda; Xin, Nini; Qiao, Zi; Chen, Suping; Zeng, Lingwan; Zhang, Yusheng; Wei, Dan; Sun, Jing; Fan, Hongsong
Abstract: Bioactive metal–organic frameworks (bio‐MOFs) built from biofunctional metal ions and linkers show a new strategy to construct multifunctional theranostic platforms. Herein, a bio‐MOF is synthetized via the self‐assembling of Fe 3+ ions and doxorubicin hydrochloride (DOX) molecules. Then, through a stepwise assembly strategy, another bio‐MOFs structure consisting of Gd 3+ ions and 1, 3, 5‐benzenetricarboxylic acid (H3 BTC) is wrapped on the surfaces of Fe‐DOX nanoparticles, followed by adsorbing photosensitizer indocyanine green (ICG). Specifically, the Gd‐MOF shell structure can not only act as a contrast agent for magnetic resonance imaging (MRI), but also provides protection for Fe‐DOX cores, controlling the release of DOX. The photoacoustic and photothermal imaging (PAI and PTI) methods are successfully introduced to the platform by loading ICG, providing potential applications for multimodal biological imaging. The in vitro and in vivo outcomes indicate that the Fe‐DOX@Gd‐MOF‐ICG nanoplatform exhibits outstanding synergistic antitumor performance via MR/PA/PT imaging guided chemotherapy, photothermal and photodynamic combination therapy. The work may encourage further exploration of bio‐MOFs based multifunctional theranostic platforms for multimodal imaging guided compound antitumor therapy, which will open an avenue of MOFs toward biological applications. Abstract : Fe‐doxorubicin hydrochloride@Gd‐metal–organic frameworks‐indocyanine green (Fe‐DOX@Gd‐MOF‐ICG (FDGI)) theranostic nanosystem with double bio‐MOFs core–shell structure is directly constructed from biologically functional metal ions and drug molecules. Taking advantage of the different functions of bio‐MOFs in the composite structure, the fabricated FDGI nanoplatform shows promising application for magnetic resonance/photoacoustic/photothermal imaging techniques guided chemo‐phototherapy.